A new strategy for development of transducers for middle ear implants. - Urquiza, Rafael; López-García, Javier (Acta Oto-Laryngologica, 2015)
Conclusion: The new strategy was efficient in designing and fabricating a new transducer for middle ear implants. The transducer could overcome important limitations (implantability of transducers, functional needs) of practical application of currently existing implants. The strategy uncovers the potential of translational research in this area of audiology. Objectives: To present an overview of research and development (R&D) strategic aspects and its practical implementation through one example of transducer development based on micro-electro-mechanical systems (MEMS) technology. Methods: (a) Rationale of technology in relation to the anatomical and functional features of the middle ear and implant requirements, (b) description and explanation of the different stages and decision-making process for the R&D of a MEMS transducer based on published pieces with their own experimental methods. Results: This R&D strategy focuses on achieving minute-size transducers by using MEMS technology. The process allows a designing-simulation-testing circle to be accomplished on the bench by special software, before fabrication and in vivo testing. The strategy, consequently, saves animal experiments, empowers the design capabilities and allows the fabrication of customized transducers for special problems. The developed prototypes are in the range of millimetres, fit the requirements of new implants and can be fabricated on a large scale and at low cost.